ChemInform Abstract: A Fast and Benign Synthesis of α‐Aminonitriles by Reusable Immobilized AlCl3 on γ‐Al2O3. Issue 22 (15th May 2015) - Pamar, M. Geeta; Govender, P.; Pillay, K.; Abrahamse, H.; Nanjundaswamy, H. M.
Abstract: AlCl3 immobilized on γ‐Al2 O3 is an efficient, safe, and environmentally friendly catalyst for the synthesis of a wide range of α‐aminonitriles (IV) via Strecker reaction.